E-business management : integration of Web technologies with business models - Shaw, Michael J (Integrated Series in Information Systems, 2002)
This text contains a collection of articles by leading information systems researchers on important topics related to the development of e-business. The goal is to enhance the understanding of the state of the art in e-business, including the most current and forward-looking research. The book emphasizes both business practices and academic research made possible by the recent rapid advances in the applications of e-business technology. The book should help graduate students, researchers, and practitioners understand major e-business developments, how they will transform businesses, and the strategic implications to be drawn.